The Category of Genderin Aspects of Comparative Grammar of Evaluation,Grammar of Creativity and Gender Linguistics:Review of the Problem(on the Material of Ukrainian and Russian Linguistic Cultures) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The reflection of the events of the reality around us is carried out in speech through the prism of the category of evaluation, which is traditionally interpreted as a consequence of the linguistic expression of logical and philosophical evaluative judgments. The article discusses the features of using the grammatical category of gender as a tool for representing axiological meanings, shades of meanings, and meanings in Ukrainian and Russian linguistic cultures, which is the subject of a comparative grammar of evaluation. The mechanisms for modelling the corresponding grammatical meanings of a semantic and pragmatic nature are described. An analysis of the factual material allows us to state numerous cases of violations of the correlation of the grammatical gender of words denoting male and female persons, which leads to the emergence of secondary semantic shades of generic forms, in particular, evaluative ones due to the linguistic creativity of native speakers. The study of grammar with a focus on axiologicalness allows us to see the dynamics in the grammatical system, forms a new look at traditional problems and, accordingly, contributes to the development of grammatical science. By filling the discourse with grammatical games, the speaker can change the axiological orientation of the statement.